2015
DOI: 10.1016/j.bandl.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age of acquisition, socioeducational status, and proficiency on the neural processing of second language speech sounds

Abstract: This study investigates the role of age of acquisition (AoA), socioeducational status (SES), and second language (L2) proficiency on the neural processing of L2 speech sounds. In a task of pre-attentive listening and passive viewing, Spanish-English bilinguals and a control group of English monolinguals listened to English syllables while watching a film of natural scenery. Eight regions of interest were selected from brain areas involved in speech perception and executive processes. The regions of interest we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 100 publications
(128 reference statements)
1
31
0
1
Order By: Relevance
“…This question reflects a binary categorical variable and does not account for type of exposure (e.g., dual language within the home vs. minority language within home and majority language within school/community), amount of exposure, proficiency (e.g., balanced vs. unbalanced bilingualism), or age of second language acquisition (early acquisition vs. later acquisition). These facets of bilingualism have been reported to impact both brain and behavioral findings (Archila-Suerte, Zevin, & Hernandez, 2015;Hoff et al, 2014;Thomas-Sunesson, Hakuta, & Bialystok, 2018;Winsler et al, 2014). Age of acquisition (AoA) in particular has been strongly associated with both behavioral differences (Luk, de Sa, & Bialystok, 2011;Sebastián-Gallés, Echeverría, & Bosch, 2005) and underlying neural correlates (Klein, Mok, Chen, & Watkins, 2014;Mohades et al, 2012Mohades et al, , 2015 related to bilingualism, and has been reported to be a better predictor of bilingual brainbehavior correlations than proficiency or exposure (Archila-Suerte et al, 2015;Sebastián-Gallés et al, 2005;Yow & Li, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This question reflects a binary categorical variable and does not account for type of exposure (e.g., dual language within the home vs. minority language within home and majority language within school/community), amount of exposure, proficiency (e.g., balanced vs. unbalanced bilingualism), or age of second language acquisition (early acquisition vs. later acquisition). These facets of bilingualism have been reported to impact both brain and behavioral findings (Archila-Suerte, Zevin, & Hernandez, 2015;Hoff et al, 2014;Thomas-Sunesson, Hakuta, & Bialystok, 2018;Winsler et al, 2014). Age of acquisition (AoA) in particular has been strongly associated with both behavioral differences (Luk, de Sa, & Bialystok, 2011;Sebastián-Gallés, Echeverría, & Bosch, 2005) and underlying neural correlates (Klein, Mok, Chen, & Watkins, 2014;Mohades et al, 2012Mohades et al, , 2015 related to bilingualism, and has been reported to be a better predictor of bilingual brainbehavior correlations than proficiency or exposure (Archila-Suerte et al, 2015;Sebastián-Gallés et al, 2005;Yow & Li, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These facets of bilingualism have been reported to impact both brain and behavioral findings (Archila-Suerte, Zevin, & Hernandez, 2015;Hoff et al, 2014;Thomas-Sunesson, Hakuta, & Bialystok, 2018;Winsler et al, 2014). Age of acquisition (AoA) in particular has been strongly associated with both behavioral differences (Luk, de Sa, & Bialystok, 2011;Sebastián-Gallés, Echeverría, & Bosch, 2005) and underlying neural correlates (Klein, Mok, Chen, & Watkins, 2014;Mohades et al, 2012Mohades et al, , 2015 related to bilingualism, and has been reported to be a better predictor of bilingual brainbehavior correlations than proficiency or exposure (Archila-Suerte et al, 2015;Sebastián-Gallés et al, 2005;Yow & Li, 2015). Unlike the binary measure of dual-language exposure, the SES measures included here (i.e., income and education) were measured as continuous variables, allowing for more variability between individuals and a higher probability of finding significant associations with both brain and cognitive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to the framework of critical period, later L2 onset age is often associated with lower L2 performance due to the maturational decay of the ability to acquire language and/or the interference of the existing linguistic system (Archila-Suerte, Zevin, Bunta, & Hernandez, 2012;Archila-Suerte, Zevin, & Hernandez, 2015;Birdsong & Molis, 2001;Newport, 1990). Although a decline in L2 capability has been demonstrated in morphology, phonology, semantics, and syntax through adulthood (Flege, Yeni-Komshian, & Liu, 1999;Johnson & Newport, 1989;Weber-Fox & Neville, 1996), age six or seven is widely thought as the general turning point and thus the cut-off between early and late bilinguals (Meisel, 2004, chap.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand how metacognition can be associated with the functions of the CE, it is worthy to contemplate what is proposed by Archilla-Suerte et al (2015). According to the researcher, although attributing different roles to selective attention and WM (i.e.…”
Section: Metacognition and The Multicomponent Model Of Working Memorymentioning
confidence: 99%